Asian development outlook 2001 - Asian Development Bank (Manila) (Hong Kong Oxford University Press, 2001)
The Asian development outlook 2000 is the Asian Development Banks annual survey of economic developments in the Asian and Pacific region.This year the outlook analysis the social challenge facing developing Asia as its enter the new millennium and it reco
Special chapter: Asias globalization challenge
Keywords: Banks and Banking; Finance; Economics; Competition, International